Higher Education Digital Leadership in Transition from Technical Adoption to Cultural Transformation - Makna Ani Marlia; Rahmat Hidayat; Zalik Nuryana (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
This study aims to systematically map the intellectual landscape of digital leadership in higher education through a comprehensive bibliometric analysis. As higher education institutions undergo accelerated digital transformation, understanding of how digital leadership has evolved, which themes dominate scholarly discourse, and where research gaps lie becomes crucial for both academic and institutional development. Using the Scopus database, 158 relevant documents from 2016 to mid-2025 were analyzed through Biblioshiny, VOS viewer, and Biblioplot to identify research trends, influential authors and institutions, and emerging thematic clusters. The results indicate that digital leadership is an increasingly relevant yet fragmented field, with dominant themes such as digital transformation, e-leadership, digital literacy, and emotional intelligence. Influential contributions have come from scholars and institutions in Europe and Southeast Asia, with the University of Patras and the University of Malaya emerging as key knowledge hubs. Thematic evolution analysis reveals a gradual shift from technology-focused leadership to more human-centered frameworks that prioritize organizational culture, emotional intelligence, and sustainability. Co-occurrence and overlay visualizations further highlight promising but underexplored areas such as principal digital leadership, digital citizenship, and regional perspectives, particularly in Africa and Asia. This study recommends that future research expands its focus to include interdisciplinary approaches and more diverse cultural contexts.